Macrotrichia, a new genus of Ledrinae (Hemiptera: Cicadellidae) from China - Zhang, Yalin; Sun, Jing; Dai, Wu (Zootaxa, 2009)
Macrotrichia gen. n., a new leafhopper genus of the tribe Ledrini (Hemiptera: Cicadellidae: Ledrinae), and three species, M. deltata sp. n., M. hamata sp. n. and M. flavomarginata (Kuoh & Cai) n. comb., from southern China are described and illustrated. A key to all species is provided, and the differences between the new genus and a closely related genus Tituria Stål are discussed.